A critique on accounting for murabaha contract: A comparative analysis of IFRS and AAOIFI accounting standards. Issue 3 (13th June 2016) - Ahmed, Mezbah Uddin; Sabirzyanov, Ruslan; Rosman, Romzie
Abstract : Purpose: The purpose of this paper is to examine the accounting treatment and reporting of a murabaha contract and its implication to the financial statements of Islamic banks. In addition, the paper also explains the implication of time value of money on the measurement of a murabaha contract and the concept of substance over form in recognising financial transactions. Design/methodology/approach: This study reviews the accounting treatment and reporting for a murabaha contract as stated in the Financial Accounting Standards (FAS) of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and the application of a murabaha contract as a financial instrument based on International Financial Reporting Standards (IFRS). Findings: The paper finds that, while IFRS-based financial reporting primarily focuses on economic consequences of financial instruments, AAOIFI further takes into consideration the legal structure of the instruments, which are based on Shari'ah precepts. The paper also finds that IFRS-based financial reporting cannot always capture the distinctive structure of the murabaha and, hence, may lack representational financial reporting. However, the IFRS recognizes the substance of a murabaha contract as financing, and the majority of Islamic banks in Malaysia report it as one of financing and not as a trading contract. For measurement, IFRS adopted the concept of time value of money where the profit allocation is based on amortized cost, which is similar to the measurement of conventional loan transactions that apply the concept of effective interest rate. Meanwhile, AAOIFI uses a straight-line basis to allocate the profit of a murabaha contract. Practical implications: The forthright discussion and the observations of the paper are expected to assist regulators and standard setters in developing accounting standards that are in convergence but also cater to the unique characteristics of Islamic financial transactions. Originality/value: The paper criticizes both accounting treatment of a murabaha contract based on the AAOIFI and IFRS and then suggests an extension of these treatments to be adopted to improve the reporting.